2021
DOI: 10.1039/d1ra06054f
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of re-dispersible dry o/w emulsions using cellulose nanocrystals decorated with metal/metal oxide nanoparticles

Abstract: Schematic diagram for the detailed preparation of dry eicosane o/w emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The re-desperation of dried eicosan emulsion in the water had no significant influence on the size of droplets. Hence, it declared that CNC surrounds the eicosan oil droplets, which, in turn, stabilizes the droplets by dint of their surface amphiphilic properties that maintain the repulsion force between the oil droplets unchanged [45].…”
Section: Emulsion Stability and Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The re-desperation of dried eicosan emulsion in the water had no significant influence on the size of droplets. Hence, it declared that CNC surrounds the eicosan oil droplets, which, in turn, stabilizes the droplets by dint of their surface amphiphilic properties that maintain the repulsion force between the oil droplets unchanged [45].…”
Section: Emulsion Stability and Characterizationsmentioning
confidence: 99%
“…Further, Umut Yucel et al studied the distribution of solutes in eicosan o/w emulsions for food systems [44]. Recently, Shaheen et al successfully prepared re-dispersible dry o/w emulsion-loaded antimicrobial silver, gold, and copper oxide nanoparticles to the eicosan/water system using eicosan as an oil phase and CNC as a stabilizing agent for the first time [45]. However, the loading of synthetic antimicrobial molecules has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the in vitro study demonstrated that BNC/AgNPs promoted wound healing of chronic ulcers by reducing microbial infection. The BNC/AgNPs were protected from oxidative stressors and played a vital role in improving cell propagation and cell proliferation [131]. The natural polyphenol compound, curcumin, which is a hydrophobic drug with antibacterial activity and wound healing ability, was encapsulated in a pluronic polymer and converted into granules.…”
Section: Cellulosementioning
confidence: 99%
“…A recently proposed approach to cellulose nanocrystal (CNC) surface charge reduction via the addition of oppositely charged colloids lacks these disadvantages . As we have shown previously, when one adds positively charged nanoparticles (TiO 2 , Al 2 O 3 , ferric oxides) to negatively charged CNC, heterocoagulation proceeds according to the mechanism of “charge neutralization–charge reversal”. Heterocoagulation helps lower ζ-potential values and adds some properties to initial polysaccharide nanocrystals, e.g., magnetic, photocatalytic, adsorptive, etc. , Recent papers on Pickering emulsions showed that stabilization by hybrid organic–inorganic is highly prospective and can add photocatalytic properties to emulsions and make them redispersible after drying . To develop emulsion-based drug delivery systems, it is necessary to use biocompatible nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Recent papers on Pickering emulsions showed that stabilization by hybrid organic−inorganic is highly prospective and can add photocatalytic properties to emulsions 14 and make them redispersible after drying. 15 To develop emulsion-based drug delivery systems, it is necessary to use biocompatible nanoparticles. Aluminum oxyhydroxide (pseudoboehmite) nanoparticles have been used as an adjuvant for over 70 years, and it plays a crucial role in drug functioning.…”
Section: Introductionmentioning
confidence: 99%